PERTANGGUNGJAWABAN KARYAWAN KANTOR NOTARIS TERKAIT MENJAGA KERAHASIAAN AKTA YANG DIBUAT OLEH NOTARIS - Sinaga, Tria Asmita Despiona; Purba, Hasim; Siahaan, Rudy Haposan (Smart Education, 2025)
Abstract: Notaries in carrying out their duties require the assistance of others, so notaries can employ people as employees in their offices with certain specifications to help fulfill their duties. The results of the research and discussion show that the legal obligation for Notary employees regarding the confidentiality of Notary deeds is not specifically regulated in the UUJN so that ethically and morally Notary employees are also obliged to keep the contents of the Notary deed confidential. The legal responsibility of Notary office employees is related to maintaining the confidentiality of Notary deeds made before a Notary, so if the Notary employee does not maintain the confidentiality of the deed, he is legally responsible and can be categorized as an unlawful act. The Notary's responsibility towards Notary employees in order to maintain the confidentiality of deeds made before a Notary in carrying out his position is that the Notary can be held civilly liable for misuse of the confidentiality of the minutes of the deed by his employees, even though in this case the notary did not make a direct mistake. Keyword: Accountability, Employees, Notary DeedsAbstrak: Notaris dalam menjalankan tugasnya memerlukan bantuan orang lain, maka notaris dapat mempekerjakan orang sebagai karyawan di kantornya dengan spesifikasi tertentu untuk membantu memenuhi tugasnya. Hasil penelitian dan pembahasan menunjukkan bahwa kewajiban hukum bagi karyawan Notaris terhadap kerahasiaan akta Notaris adalah tidak diatur secara khusus dalam UUJN sehingga secara etika dan moral karyawan Notaris juga berkewajiban merahasiakan isi akta Notaris tersebut. Tanggungjawab hukum karyawan kantor Notaris terkait menjaga kerahasiaan akta Notaris yang dibuat dihadapan Notaris, maka apabila pegawai notaris tidak menjaga kerahasiaan akta bertanggung jawab secara hukum dan dapat dikateogrikan sebagai perbuatan melawan hokum. Pertanggungjawaban Notaris terhadap karyawan Notaris dalam rangka menjaga kerahasiaan akta yang dibuat dihadapan Notaris dalam menjalankan jabatannya adalah Notaris dapat dipertanggungjawabkan secara perdata akibat penyalahgunaan kerahasiaan minuta akta oleh pekerjanya, meskipun dalam hal ini notaris tidak melakukan kesalahan secara langsung. Kata kunci: Pertanggungjawaban, Karyawan, Akta Notaris